Schrems II: The EU’s Influence on U.S. Data Protection and Privacy Laws - Donna Calia (Washington University Global Studies Law Review, 2022)
The United States and European Union have been deeply connected since the EU’s formation in 1957. Although international trade is a hallmark of the U.S. and EU’s relationship, the two have struggled throughout history to align their laws and objectives, despite a collection of evolving international trade agreements. That said, the U.S. and EU’s trade relationship is considered to be the “world’s largest and most important bilateral commercial relationship.” The Transatlantic Economy accounts for 16 million jobs, trillions of dollars in total commercial sales, and one third of the total gross domestic product in terms of purchasing power. More recently, the digital revolution has posed a threat to the Transatlantic Economy, revealing fundamental differences in U.S. and EU law. To harmonize U.S. and EU law, the respective countries have entered into numerous trade agreements to maximize transatlantic data transfers. The EU leverages the importance of the Transatlantic Economy to encourage the U.S. to comply with EU law through numerous court decisions directly targeting the inadequacy of U.S. domestic law compared to the General Data Protection Regulation (“GDPR”) and EU Charter. With each international trade agreement and landmark decision, the EU has influenced the U.S. to alter its approach, proving the EU’s power as a progressive leader in data protection and privacy laws. This note chronicles previous U.S.-EU trade agreements and the landmark cases ordering their invalidations to demonstrate the EU’s influence on the advancement of U.S. data protection and privacy law.